Identification of ZBTB26 as a novel risk factor for congenital hypothyroidism - Vick, Philipp; Fredershausen, Birgit; Choukair, Daniela; Weiß, Birgit; Röth, Ralph; Schneider, Isabelle; Paramasivam, Nagarajan; Bettendorf, Markus; Rappold, Gudrun (Genes, 2021)
Congenital primary hypothyroidism (CH; OMIM 218700) is characterized by an impaired thyroid development, or dyshormonogenesis, and can lead to intellectual disability and growth retardation if untreated. Most of the children with congenital hypothyroidism present thyroid dysgenesis, a developmental anomaly of the thyroid. Various genes have been associated with thyroid dysgenesis, but all known genes together can only explain a small number of cases. To identify novel genetic causes for congenital hypothyroidism, we performed trio whole-exome sequencing in an affected newborn and his unaffected parents. A predicted damaging de novo missense mutation was identified in the ZBTB26 gene (Zinc Finger A and BTB Domain containing 26). An additional cohort screening of 156 individuals with congenital thyroid dysgenesis identified two additional ZBTB26 gene variants of unknown significance. To study the underlying disease mechanism, morpholino knock-down of zbtb26 in Xenopus laevis was carried out, which demonstrated significantly smaller thyroid anlagen in knock-down animals at tadpole stage. Marker genes expressed in thyroid tissue precursors also indicated a specific reduction in the Xenopus ortholog of human Paired-Box-Protein PAX8, a transcription factor required for thyroid development, which could be rescued by adding zbtb26. Pathway and network analysis indicated network links of ZBTB26 to PAX8 and other genes involved in thyroid genesis and function. GWAS associations of ZBTB26 were found with height. Together, our study added a novel genetic risk factor to the list of genes underlying congenital primary hypothyroidism and provides additional support that de novo mutations, together with inherited variants, might contribute to the genetic susceptibility to CH.